If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.36x + 64 = 11.2896 + 8x Reorder the terms: 64 + 3.36x = 11.2896 + 8x Solving 64 + 3.36x = 11.2896 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 64 + 3.36x + -8x = 11.2896 + 8x + -8x Combine like terms: 3.36x + -8x = -4.64x 64 + -4.64x = 11.2896 + 8x + -8x Combine like terms: 8x + -8x = 0 64 + -4.64x = 11.2896 + 0 64 + -4.64x = 11.2896 Add '-64' to each side of the equation. 64 + -64 + -4.64x = 11.2896 + -64 Combine like terms: 64 + -64 = 0 0 + -4.64x = 11.2896 + -64 -4.64x = 11.2896 + -64 Combine like terms: 11.2896 + -64 = -52.7104 -4.64x = -52.7104 Divide each side by '-4.64'. x = 11.36 Simplifying x = 11.36
| 24=a-15 | | 9x+8=9(x-4) | | 5x-1=7x+1 | | 3/4x^2-1/3x-1=0 | | 4x-6=5x-8 | | 6q-17=30 | | 2x^2+10x-50=0 | | 5h+11-2h=50 | | 40+3x=180-x^2-2x | | M+6=12+15 | | 42.72=.99x+27 | | 6(2x+2)+12=50 | | 14n-32=22 | | 5z=26 | | 2x-14+3(x+1)=-4 | | 98-2x=3x+22 | | 5x=2x^2+5x-50 | | 23+4(x-3)-x=11 | | 3x^2-9y=4 | | -6x+21+8x+21=6 | | 30-6(x+3)+2x=8 | | 42.72=15.99x+27 | | n(x)+3=72(76)x(y)+z | | x=1-1+1-1+1-1+1*1 | | 10.5+h=22.5 | | (n-5)*10=80 | | 60-5x=12-7x | | 0.05s+.1(6000-s)=375 | | 2(4x-2)-5x=-18 | | n-5*10=80 | | -29-10(15)=-18(15)+91 | | 5(2x+1)+4(3x-2)= |